A gestão do conhecimento no corpo de intendentes da Marinha do Brasil: desafios e oportunidades na busca pela excelência da aprendizagem organizacional - Parreira, Thiago José (2013)
This study builds on the theories of Knowledge Management (KM) and identifies the hurdles and challenges faced by the military organizations within Brazilian Navy responsible for applying the principles of the Neptune Program in the education, specialization, and training of Supply Officers. Initially, we examine relevant concepts on Knowledge Management and pinpoint their importance to Public Administration, particularly to hierarchical organizations such as the Armed Forces. Later on, we provide a brief contextualization of the theories of KM based on the organizational structure of the Brazilian Navy Quartermasters Corps and the current principles of the Neptune Program. We also highlight the continuous pursuit for excellence in Public Administration as a source of inspiration to fostering the consolidation of KM within organizations. The utilization of qualitative research methods allows for an accurate understanding of the tenets of KM and brings to the forefront the major facilitators and barriers to knowledge sharing in professional environments. This approach enables the identification of the main practical tools observed in the fieldwork and does not deprive oneself from bringing up different tools haply suggested by the respondents. Subsequently, this study makes evident that the Neptune Program, whose website may be regarded as a virtual environment of knowledge sharing, has the necessary requirements to take over the role of a provider of a shared space for knowledge creation - 'Ba'. In this sense, one may infer that the Neptune Program provides solid opportunities to consolidate KM within Brazilian Navy Quartermaster Corps. Finally, this work concludes that the Admiral Newton Braga Instruction Center (CIANB) has an outstanding potential to become the 'Corporate University for the Quartermaster Corps' in the near future.